Fire fighter - Goldberg, Jan (Mankato, Minnesota : Capstone Press, 1999)
Outlines the educational requirements, duties, salary, employment outlook, and possible future positions for fire fighters.
Includes bibliographical references and index.
Keywords: Fire extinction -- Vocational guidance -- Juvenile literature; Fire prevention -- Vocational guidance -- Juvenile literature; Fire fighters -- Juvenile literature